Sleep apnea severity stratification by an FFT-based PPG-derived index - Cajal Orleans, Diego; Gil, Eduardo; Laguna, Pablo; Varon, Carolina; Testelman, Dries; Buyse, Bertien; Jensen, Chris; Hoare, Rohan; Bailón, Raquel; Lázaro, Jesús (Jornada de Jóvenes Investigadores del I3A, 2022)
A new index for sleep apnea stratification is proposed. This index is based on the detection of the frequencies at which cyclic variations of the heart rate (CVHR) occur in segments with abnormal breathing. A CVHR detector is also proposed. When this detector is used, the proposed index has a correlation of r = 0.68 with the apnea-hypopnea index. The absence of correlation when the CVHR detector is not used suggests that CVHR detection is necessary for a correct evaluation.